2022
DOI: 10.1038/s41467-022-31250-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell-derived extracellular vesicles promote CD8+ T cell exhaustion via TGF-β type II receptor signaling

Abstract: Cancer immunotherapies have shown clinical success in various types of tumors but the patient response rate is low, particularly in breast cancer. Here we report that malignant breast cancer cells can transfer active TGF-β type II receptor (TβRII) via tumor-derived extracellular vesicles (TEV) and thereby stimulate TGF-β signaling in recipient cells. Up-take of extracellular vesicle-TβRII (EV-TβRII) in low-grade tumor cells initiates epithelial-to-mesenchymal transition (EMT), thus reinforcing cancer stemness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 71 publications
3
49
0
1
Order By: Relevance
“…How tEVs activate these pathways remains unclear, yet we found that they contain several regulators of the TGFß pathway (Smad5, Smurf2, etc.) (Ghoroghi et al, 2021b), including TGFß type II receptor, whose presence on tEVs is sufficient to trigger the pathway in receiving cells (Xie et al, 2022). Altogether, we demonstrate here that blood flow and tEVs cooperate to favor lysosomal escape allowing tEVs to promote a pronounced pro-angiogeneic transcriptional program in endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…How tEVs activate these pathways remains unclear, yet we found that they contain several regulators of the TGFß pathway (Smad5, Smurf2, etc.) (Ghoroghi et al, 2021b), including TGFß type II receptor, whose presence on tEVs is sufficient to trigger the pathway in receiving cells (Xie et al, 2022). Altogether, we demonstrate here that blood flow and tEVs cooperate to favor lysosomal escape allowing tEVs to promote a pronounced pro-angiogeneic transcriptional program in endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, endothelial tEVs were shown to activate the Notch pathway in endothelial cells, resulting in increased expression of HEY1 and HEY2 and formation of capillary-like structures in vitro and in vivo (Sheldon et al, 2010). In addition, activation of the TGFß pathway in endothelial cells promotes inflammation and endothelial permeabilization (Chen et al, 2019), while the presence of TGFß type II receptor on tEVs correlates with metastasis (Xie et al, 2022). While pro-angiogenic programs, which could possibly be activated by the Notch and TGFß pathways, require a concerted action of flow and tEVs uptake in endothelial cells, whether they impact the angiogenic activity of endothelial cells remained unsolved.…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown of TGFBR2 will damage cell proliferation and migration, and inhibition of these two genes will inhibit angiogenesis, which provides a strategy for the treatment of breast cancer. The levels of TGFBR2 circulating extracellular vesicles (crEV) appears to correlate with tumor burden, metastasis and patient survival, thereby serve as a non-invasive screening tool to detect malignant breast tumor stages [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, improved immune checkpoint inhibition by targeting SPHK1/S1P signaling has potential clinical application in ovarian cancer. Xie F et al [ 55 ] observed that breast cancer cells secrete TEV enriched in active TGF-β type II receptor (TβRII) which transfer to CD8 + T cells induced the activation of transforming growth factor-beta signaling protein 3 (SMAD3). SMAD3 cooperates with transcription factor TCF1 to promote CD8 + T cell exhaustion.…”
Section: Evs and Tumor Immune Suppressionmentioning
confidence: 99%